2011
DOI: 10.1111/j.1745-4565.2010.00282.x
|View full text |Cite
|
Sign up to set email alerts
|

AQUEOUS EXTRACTS FROM THE BULBS OF TULBAGHIA VIOLACEA ARE ANTIFUNGAL AGAINST ASPERGILLUS FLAVUS

Abstract: Aspergillus flavus is a cosmopolitan fungal pathogen that is often implicated in food spoilage and in aspergillosis infections in immunocompromised individuals. The current study was undertaken to assess the effect of aqueous bulb extracts of Tulbaghia violacea on A. flavus spore survival. The broth dilution assay was used to determine that the minimum inhibitory concentration (MIC) of the extract against A. flavus was 15 mg/mL and that the minimum fungicidal concentration (MFC) was 20 mg/mL. During well diffu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In at least one case, both fungal growth and mycotoxin production in A. parasiticus (18) was inhibited by plant essential oils. In various studies, T. violácea extracts exhibited antifungal activity against a variety of fungi (5,9,13,14). In various studies, T. violácea extracts exhibited antifungal activity against a variety of fungi (5,9,13,14).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In at least one case, both fungal growth and mycotoxin production in A. parasiticus (18) was inhibited by plant essential oils. In various studies, T. violácea extracts exhibited antifungal activity against a variety of fungi (5,9,13,14). In various studies, T. violácea extracts exhibited antifungal activity against a variety of fungi (5,9,13,14).…”
Section: Resultsmentioning
confidence: 99%
“…Cultivated T. violácea plants were obtained, and aqueous extracts were made as previously described (5). Cultivated T. violácea plants were obtained, and aqueous extracts were made as previously described (5).…”
Section: Methodsmentioning
confidence: 99%
“…Because of prolonged or overuse of some fungicides, many plant pathogens have developed resistance toward many synthetic chemicals, thereby rendering the fungicide ineffective (PÉRET-ALMEIDA et al, 2008;BELEWA et al, 2011;MEDEIROS et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…However, there are considerable discrepancies in the antimicrobial assay results reported. Whereas some authors have found the plant to be completely devoid of antimicrobial activity (McGaw et al, 2000;Bamuamba et al, 2008;Nyila et al, 2012), others have observed significant antimicrobial properties in various Tulbaghia extracts (Motsei et al, 2003;Lindsey and Van Staden, 2004;Thamburan et al, 2006;Nteso and Pretorius, 2006a,b;Buwa and Afolayan, 2009;Belewa et al, 2011;Somai and Belewa, 2011;Jäger and Stafford, 2012;Soyingbe et al, 2013).…”
Section: Introductionmentioning
confidence: 95%